Extended Spectrum Beta-lactamase producing Salmonella Lindenberg gastroenteritis - Rajan Prabhurajan; Rajasekharapanicker Kiran; Kesavaram Padmavathy (Journal of Infection in Developing Countries)
Introduction: Increasing antimicrobial resistance among non-typhoidal Salmonella (NTS) is a major public health issue especially in developing countries and is partly due to the use of antimicrobials in animal feeds as growth promoters. NTS are often associated with self-limiting acute gastroenteritis (AGE). Nevertheless, fluoroquinolones and third-generation cephalosporins are currently used in the treatment of severe diarrhoeal infections.